2015
DOI: 10.3832/ifor1307-007
|View full text |Cite
|
Sign up to set email alerts
|

Links between phenology and ecophysiology in a European beech forest

Abstract: © iForest -Biogeosciences and Forestry IntroductionAt scales ranging from organ to ecosystem, many processes, particularly those related to carbon cycling (productivity and growth), water (evapotranspiration and runoff), and nutrients (decomposition and mineralization), are directly mediated by phenology (Gu et al. 2003). Spring bud burst provides a particularly good example, as it involves various interactions between trees and the environment. The initiation of this phenological phase depends on early spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
(56 reference statements)
0
5
2
Order By: Relevance
“…This has been demonstrated in the case study loaded in DevX. Studies where both approaches, dendrometer, and histological measurements are combined are still scarce, mostly focusing on conifers in temperate (Michelot et al, 2012;Cuny et al, 2015;Urban et al, 2015), Mediterranean (Camarero et al, 2009;Linares et al, 2009; Vieira et al, 2014a,b;Pacheco et al, 2016;Güney et al, 2017), and boreal forests (Chan et al, 2016) or mountain ranges (Ziaco and Biondi, 2016). Some examples of the use of band dendrometers and xylogenesis analysis in the tropics also exist (Mendivelso et al, 2016).…”
Section: Dendrometer and Microcore Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…This has been demonstrated in the case study loaded in DevX. Studies where both approaches, dendrometer, and histological measurements are combined are still scarce, mostly focusing on conifers in temperate (Michelot et al, 2012;Cuny et al, 2015;Urban et al, 2015), Mediterranean (Camarero et al, 2009;Linares et al, 2009; Vieira et al, 2014a,b;Pacheco et al, 2016;Güney et al, 2017), and boreal forests (Chan et al, 2016) or mountain ranges (Ziaco and Biondi, 2016). Some examples of the use of band dendrometers and xylogenesis analysis in the tropics also exist (Mendivelso et al, 2016).…”
Section: Dendrometer and Microcore Studiesmentioning
confidence: 91%
“…Considering work performed outside this area, most studies where both monitoring methods are applied have found a delay in wood formation phenological phases, when compared to dendrometer records (Mäkinen et al, 2008;Michelot et al, 2012;Güney et al, 2017), which might be partly ascribed to differentiation and production of phloem (e.g., Gričar et al, 2009Gričar et al, , 2016. Urban et al (2015), although not comparing growth curves of both monitoring approaches, found that the growth begin in dendrometers coincided with histological observations in a pure beech forest. In conifers, according to Mäkinen et al (2008), growth dynamics can systematically lag more than a week behind for microcores when compared to dendrometer records.…”
Section: Case Study-xylem Phenology Of Central European Temperate Trementioning
confidence: 94%
See 1 more Smart Citation
“…The upscaling of the tree sap flow to the forest stand level was performed using the regression between the tree diameter at 1.3 m (DBH) and the corresponding sap flow (Čermák et al, ; Urban et al, ). First, the DBHs of all trees of the experimental plot (608 m 2 ) were measured, and based on these values, the trees were divided into the diameter classes (with a step of 3 cm).…”
Section: Methodsmentioning
confidence: 99%
“…For temperate tree species, this begins in spring and tails off in late summer. Most studies indicate that for temperate trees, the length of growing season as regards radial growth is 60-100 days, with cessation occurring in most trees during July or August (Schmitt et al, 2016;Studhalter, Glock, & Agerter, 1963;Urban et al, 2014). Castillo et al (2016), however, compared the phenology of xylem formation in Fagus sylvatica and Pinus sylvestris at various locations in Europe with differing altitudes.…”
Section: The Phenology Of Xylogenesismentioning
confidence: 99%